Agents for the treatment of rheumatic diseases - Zimmermann-Górska, Irena (Przewodnik Lekarza/Guide for GPs, 2007)
Characteristics of the TNF-α blocking agents (infliximab, etanercept, adalimumab), IL-1 blocking agent (anakinra), costimulatory blocking agent (abatacept) and anti-CD20 monoclonal antibody (rituximab), their efficacy in the most frequent inflammatory rheumatic diseases, their toxicity as well as the emerging biological therapies, are presented.